Impact of sustainable development goal orientation on supply chain collaboration and sustained competitive advantage: Evidence from the tea and coffee industry - Benjenop Buranasiri; Po-Lin Lai; Suhan Woo; Pairach Piboonrungroj (Asian Journal of Shipping and Logistics (AJSL), 2024)
According the Resource Based View (RBV) theory and the sustainable development goals (SDG) framework, this study investigates the structural relationships between sustainable development goals, supply chain collaboration, and sustained competitive advantage. Data were collected from a survey of 359 firms in Thailand's coffee and tea supply chains and analyzed using structural equation modeling. The findings show that partnership is the most influential aspect of the SDG, whereas resource sharing is the most influential aspect of supply chain collaboration. Findings also show that supply chain collaboration has more influence than capability to enhance sustained competitive advantage. This research sheds light on the linkage between sustainable development goals and supply chain collaboration and capability, which affects the firm's sustained competitive advantage.
Keywords: 650; Supply chain collaboration; Sustainable development goals; Sustained competitive advantage; Coffee supply chain